2021
DOI: 10.1021/acssuschemeng.1c01284
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Approach for Product Portfolio Optimization: Waste to Added-Value Products

Abstract: A multi-stage multilayer systematic procedure has been developed for the selection of the optimal product portfolio from waste biomass as feedstock for systems involving water-energy-food nexus. It consists of a hybrid heuristic, metric based, and optimization methodology that evaluates the economic and environmental performance of added value products from a particular raw material. The first stage preselects the promising products. Next, a superstructure optimization problem is formulated to valorize or tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…It has been reported that 1463 g of polyphenols, representing 85% of the initial phenolic content, can be extracted from 1000 L of OMWW by membrane technologies (Bazzarelli et al., 2016). In another study, the quantity of polyphenols recovered from alperujo can reach 46 g/s over 4 months of processing (Guerras et al., 2021). On the other hand, the investment for polyphenol recovery units of alperujo and olive leaves and branches is around €110.2 million for 100 kilotons/year, while the profit can reach €14.5 million/year when olive byproducts are purchased (€249/ton for alperujo and €6/ton for olive leaves and branches) or €34.3 million/year when phenol recovery processes are attached to an olive oil production facility (Guerras et al., 2021).…”
Section: Applications Of Active Compounds From Olive Byproducts In Fo...mentioning
confidence: 97%
See 1 more Smart Citation
“…It has been reported that 1463 g of polyphenols, representing 85% of the initial phenolic content, can be extracted from 1000 L of OMWW by membrane technologies (Bazzarelli et al., 2016). In another study, the quantity of polyphenols recovered from alperujo can reach 46 g/s over 4 months of processing (Guerras et al., 2021). On the other hand, the investment for polyphenol recovery units of alperujo and olive leaves and branches is around €110.2 million for 100 kilotons/year, while the profit can reach €14.5 million/year when olive byproducts are purchased (€249/ton for alperujo and €6/ton for olive leaves and branches) or €34.3 million/year when phenol recovery processes are attached to an olive oil production facility (Guerras et al., 2021).…”
Section: Applications Of Active Compounds From Olive Byproducts In Fo...mentioning
confidence: 97%
“…In comparison with synthetic antioxidants, antioxidant compounds extracted from olive processing residues may suffer from several limitations including reduced efficiency, higher incorporation levels, bad smell and taste, lower stability during processing, and higher prices. For instance, the prices of HT and oleuropein obtained by adsorption are approximately €300/1 kg and €850/1 kg (Guerras et al., 2021). However, the increased consumer awareness of safety issues related to synthetic antioxidants, the health benefits offered by natural antioxidants, and the high disposal costs of olive processing residues prompt development of sustainable processes for the recovery and valorization in food packaging of active compounds from olive processing residues, especially polyphenols.…”
Section: Applications Of Active Compounds From Olive Byproducts In Fo...mentioning
confidence: 99%
“…Plant extracts are widely used for the production of novel therapeutic drugs against a number of ailments [ 1 , 2 ]. Solvents, such as ethanol, methanol and water, are extensively used for the extraction of valuable compounds of different origin [ 10 , 35 , 36 , 37 , 38 ]. The results of the present study show that these solvents were very effective and could mediate the beneficial effects of the plant E. arvense L., at least in the case of its cytogenotoxic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Filippini et al (2019) reported design and economic evaluation of solar-powered hybrid multi effect and reverse osmosis system for seawater desalination. Also, Sanchez et al (2019) have shown the utilization of captured CO2 hydrogenation with green hydrogen for methanol, ammonia and urea productions, while, Guerras et al (2021) proposes that biomass as a renewable resource should be devoted for the production of added value products (for example, in the pharma, food additives, health sectors) and only wastes should be used for energy production. Evaluation of these new technologies should also consider operational flexibility (Mitsos et al, 2018) as well as safety (Eini et al, 2016).…”
Section: Sustainable Process Networkmentioning
confidence: 99%